An analytical performance approach for RCS/RS with one robot serving multiple stack heights under a one-path relocation strategy - Philipp Trost; Michael Eder (Scientific Reports, 2024)
Abstract Robotic compact storage and retrieval systems (RCS/RS) represent a modern and useful storage system since the number of installed systems is growing fast. The modularity and demand-based scalability are reasons, therefore. Nonetheless, there are hardly any statements on the performance of those warehouses. This paper presents an analytical calculation approach to determine the performance of an RCS/RS with one operating robot serving different grid sizes and a varying number of stacked containers. The robot’s cycle time is calculated by assuming a uniform distribution of container stacks and a probabilistic storage height. A discrete-event simulation model of an RCS/RS is built to verify and validate the analytical approximations. The system’s basic structure and the input parameters originate from a European material handling provider. After the verification and validation, an extensive parameter variation is done with the target of displaying a wide range of usage. This analytical approach, which is easy and fast solvable with standard calculation programs, represents an easy and fast tool to predict the performance of one robot operating in an RCS/RS for any system configuration.